Performing Factuality in John Dunton’s Athenian Cosmos: The Rites of Truth - Jasenowski, Jaroslaw (Palgrave Macmillan, 2024)
Starting from the fundamental epistemological shifts characterising the seventeenth century, this book explores the re-conceptualization of the notion of truth and asks how factuality, along with other truth-carrying discourses, was appropriated by a range of texts to generate credibility. Tracing the numerous ways in which authors such as John Dunton, Charles Gildon, François Perreaud, Thomas Brown, or Joseph Addison and Richard Steele deliberately toyed with the truth effects generated by their participation in discourses such as proto-science, medicine, philosophy, law and religion, this monograph argues that truth is not a monolithic constant. Performing Factuality proposes that truth is protean, ever- emerging from a simultaneously conventionalised yet constantly mutating set of practices, something which not simply is but something which is actively done. This performative dimension finds one of its most powerful examples in the case of Dunton and his handful of collaborators working on the Athenian Mercury, which set the tone in periodical publication for decades if not centuries to come.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 17th Century Literature; Athenian Cosmos; Athenian Society; Coffeehouse Culture; Daniel Defoe; John Dunton; Periodical Publication; Restoration